EFFICACY AND RESISTANCE PATTERN OF SOME COMMONLY USED INSECTICIDES AGAINST ANOPHELES MOSQUITOES IN SIX LOCAL GOVERNMENT AREAS OF ADAMAWA STATE, NORTHEASTERN NIGERIA - Augustine, L. M.; Pukuma, M. S.; Daniel, J. L.; Vandi, P.; Enock, N.; Kunihya, I. Z. (FUDMA JOURNAL OF SCIENCES, 2024)
The global effort to control malaria vectors has been halted due to resistance mechanisms developed against various insecticides and their associated effects. This study evaluates the efficacy and resistance pattern of some commonly used insecticides against Anopheles mosquitoes using various insecticide concentrates. A ladle was used to collect Anopheles mosquito larvae in the study areas. The collected larvae were transferred to a plastic container and transported to the Institute of Infectious Diseases of Poverty (IIDP) laboratory in Modibbo Adama University, Yola, where the samples were reared to adulthood. Four separate batches of twenty-five (25) female Anopheles mosquitoes were subjected to the test papers of each impregnated insecticide for 1 hour at 27± 1°C and 80± 2% relative humidity. Similar batches were subjected to the non-impregnated insecticide paper as a control. After one hour of subjection, they were conveyed into a holding tube furnished with cotton drenched with a 10% sugar solution. Following 24 hours, mortality and susceptibility were observed and recorded. The findings showed that propoxur, bendiocarb, and pirimiphos-methyl showed 100% susceptibility across all Local Government Areas studied. In contrast, permethrin, deltamethrin, and DDT showed resistance across the Local Government Areas suggesting varying significant resistance levels. These findings outrageously emphasize the significance of ongoing surveillance, resistance management, and context-specific development for vector control strategies to combat malaria effectively in Adamawa state.